ActionScript developer's guide to Robotlegs - Hooks, Joel (O'Reilly, 2011)
Robotlegs is a standout among the ActionScript 3 development frameworks available today. With it, Flash, Flex, and AIR developers can create well-architected, testable, and flexible Rich Internet Applications--fast. This concise guide shows you how the light footprint and focused scope of this open source framework not only solves your immediate coding problems, it helps you gain insight into AS3 architecture on a much deeper level. The authors provide a walkthrough of specific features in two applications they've written in Robotlegs, complete with code for each application as a whole. You'll l.